COMPUTER SIMULATION OF DETERMINING SILTATION VOLUMES OF WATER RESERVOIR STORAGE ON THE AKSAY RIVER - M. R. Magomedova; Z. A. Kurbanova; B. A. Shangereeva (Вестник Дагестанского государственного технического университета: Технические науки)
Objectives. The development of a mathematical model for the increased turbidity zones of the Aksay river in order to determine the siltation volumes of the Aksay water reservoir storage.Method. The mathematical model is developed using the theory of probability and the theory of random process outliers. The model takes the normal distribution of the horizontal and vertical components of the instantaneous flow velocities into account, as well as the Rayleigh law of the distribution of their maxima. The proposed model is used to calculate the “turbidity tail” of the Aksay river.Result. Due to the multifactorial nature of the continuously associated processes of siltation and deposition of suspended and bottom sediments in the upper pounds of the Aksay reservoir storage hydrological system, a mathematical model of the reservoir accretion process is developed. This model provides the reliability of accretion forecasting with spatial and temporal correlation with the siltation process model, which is actually feasible on the basis of computer simulation.Conclusion. The developed model, which is based on a probabilistic approach and the theory of random process outliers, reflects the overall process of sediment transport in open channels. The development and execution of simulation programmes is carried out using the Microsoft Developer Studio (MDS) and the Fortran Power Station algorithmic language, which comprises not only a programming system, but also a set of tools for supporting large software projects integrated into MDS.